Temperament, plasticity, and emotions in defensive behaviour of paca (Mammalia, hystricognatha) - Nogueira, Selene S. C.; Nogueira-Filho, Sérgio L. G.; Duarte, José M. B. [UNESP]; Mendl, Michael (MDPI, 2021)
Within a species, some individuals are better able to cope with threatening environments than others. Paca (Cuniculus paca) appear resilient to over-hunting by humans, which may be related to the behavioural plasticity shown by this species. To investigate this, we submitted captive pacas to temperament tests designed to assess individual responses to short challenges and judgement bias tests (JBT) to evaluate individuals’ affective states. Results indicated across-time and context stability in closely correlated “agitated”, “fearful” and “tense” responses; this temperament dimension was labelled “restless”. Individual “restless” scores predicted responses to novelty, although not to simulated chasing and capture by humans in a separate modified defence test battery (MDTB). Restless animals were more likely to show a greater proportion of positive responses to an ambiguous cue during JBT after the MDTB. Plasticity in defensive behaviour was inferred from changes in behavioural responses and apparently rapid adaptation to challenge in the different phases of the MDTB. The results indicate that both temperament and behavioural plasticity may play a role in influencing paca responses to risky situations. Therefore, our study highlights the importance of understanding the role of individual temperament traits and behavioural plasticity in order to better interpret the animals’ conservation status and vulnerabilities.
Keywords: Behaviour; Cognitive bias; Escape behaviour; Personality; Stress; Temperament